Restorative justice in juvenile justice systems: a comparative study of Indonesia and Belgium - Ashari Kurniawan (Jurnal Konseling dan Pendidikan, 2025)
This study examines the implementation of restorative justice through diversion mechanisms in Indonesia’s juvenile criminal justice system, compared with practices in Belgium. Using a juridical-comparative approach, the research analyzes legislation, international legal instruments, and relevant academic literature. The focus is on diversion policy, community involvement, and institutional challenges in applying restorative justice. The findings reveal that Indonesia has a strong normative foundation through the Juvenile Criminal Justice Law (2012) and Government Regulation No. 58/2022, which substantively align with the cultural value of musyawarah (deliberation). However, implementation remains hindered by regulatory overlaps, weak institutional capacity, and limited community participation. In contrast, Belgium demonstrates a more established system, with a clear separation between juvenile and adult justice, strong institutional support, and consistent application of diversion as a primary response to juvenile delinquency. The comparison highlights that although Indonesia possesses cultural compatibility with restorative justice, its implementation lags significantly behind Belgium. This study contributes to legal scholarship by offering concrete recommendations are harmonizing conflicting regulations, strengthening the capacity of LPKS and probation institutions, enhancing the role of law enforcement in facilitating diversion, and empowering communities through legal awareness. The findings reaffirm the need to shift from punitive approaches toward child protection and reintegration as the core principle of restorative justice.